2019
DOI: 10.1111/trf.15534
|View full text |Cite
|
Sign up to set email alerts
|

Approaching treatment of transplant‐associated thrombotic Microangiopathy from two directions with Eculizumab and transitioning from Tacrolimus to Sirolimus

Abstract: BACKGROUND In the past, conventional treatment strategies for transplant‐associated thrombotic microangiopathy (TA‐TMA) have not proven to be very effective. Recently, eculizumab which is a humanized monoclonal antibody that works as a terminal complement inhibitor has demonstrated promise in the treatment landscape of TA‐TMA. METHODS AND MATERIALS This was a single‐center retrospective analysis of 20 consecutive adult patients with TA‐TMA: 10 patients who received conventional therapy and 10 patients who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Only three patients transitioned from tacrolimus to sirolimus due to TA‐TMA alone. All three patients received treatment with eculizumab, a humanized monoclonal antibody, which has demonstrated clinical efficacy for TA‐TMA 15 . Two patients had resolution at 30‐ and 90‐day assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three patients transitioned from tacrolimus to sirolimus due to TA‐TMA alone. All three patients received treatment with eculizumab, a humanized monoclonal antibody, which has demonstrated clinical efficacy for TA‐TMA 15 . Two patients had resolution at 30‐ and 90‐day assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients had resolution at 30‐ and 90‐day assessment. With this small subset, it is difficult to evaluate the efficacy of transition from tacrolimus to sirolimus for TA‐TMA resolution; however, we have reported our experience with TA‐TMA previously 15 …”
Section: Discussionmentioning
confidence: 99%
“…The Eculizumab group was treated with Eculizumab, immunosuppression, therapeutic plasma exchange and/or other supportive care measures. Another study by Jan et al [ 70 ] reported 80% hematologic (defined as normalization of LDH, the disappearance of schistocytes and improvement in transfusion requirements at 4 weeks after initiation of TA-TMA therapy) or complete response (defined as hematologic response with organ recovery) rates with the use of Eculizumab (dosed as in aHUS), compared to 0% in the conventional treatment group. The Eculizumab therapy was accompanied by a change in immunosuppression (from tacrolimus to sirolimus), whereas 7 out of 12 patients received Eculizumab maintenance.…”
Section: Current Therapeutic Approachesmentioning
confidence: 99%
“…At MD Anderson, in 5 years, 10 patients received in an uncontrolled and retrospective study [187]. The anti-complement agent was associated with a change in immunosuppression.…”
Section: Anti-complement Agentsmentioning
confidence: 99%